Results of 15 Gy HDR-BT boost plus EBRT in intermediate-risk prostate cancer: Analysis of over 500 patients. (December 2019) - Martell, K.; Mendez, L.C.; Chung, H.T.; Tseng, C.L.; Alayed, Y.; Cheung, P.; Liu, S.; Vesprini, D.; Chu, W.; Wronski, M.; Szumacher, E.; Ravi, A.; et al.
Highlights: 5-year FFBF was 92% in patients with intermediate risk prostate cancer treated with 15 Gy HDR boost. 5-year MFS was 96% in patients with intermediate risk prostate cancer treated with 15 Gy HDR boost. Abstract: Purpose/objective: To report biochemical control associated with single fraction 15 Gy high-dose-rate brachytherapy (HDR-BT) boost followed by external beam radiation (EBRT) in patients with intermediate-risk prostate cancer. Materials and methods: A retrospective chart review of all patients with intermediate-risk disease treated with a real-time ultrasound-based 15 Gy HDR-BT boost followed by EBRT between 2009 and 2016 at a single quaternary cancer center was performed. Freedom from biochemical failure (FFBF), cumulative incidence of androgen deprivation therapy use for biochemical or clinical failure post-treatment (CI of ADT) and metastasis-free survival (MFS) outcomes were measured. Results: 518 patients met the inclusion criteria for this study. Median age at HDR-BT was 67 years (IQR 61–72). 506 (98%) had complete pathologic information available. Of these, 146 (28%) had favorable (FIR) and 360 (69%) had unfavorable (UIR) intermediate-risk disease. 83 (16%) received short course hormones with EBRT + HDR. Median overall follow-up was 5.2 years. FFBF was 91 (88–94)% at 5 years. Five-year FFBF was 94 (89–99)% and 89 (85–94)% in FIR and UIR patients, respectively ( p = 0.045). CI of ADT was 4 (2–6)% at 5 years. Five-year CI of ADT was 1 (0–3)% and 5 (2–8)% in FIR and UIR patients, respectively ( p = 0.085). MFS was 97 (95–98)% at 5 years. Five-year MFS was 100 (N/A-100)% and 95 (92–98)% in FIR and UIR patients, respectively ( p = 0.020). Conclusion: In this large cohort of intermediate-risk prostate cancer patients, 15 Gy HDR-BT boost plus EBRT results in durable biochemical control and low rates of ADT use for biochemical failure.